La jurisprudencia de Derechos Humanos en la Argentina - Manzi, Adrian (Nómadas. Critical Journal of Social and Juridical Science, 2013)
In this work there will be mentioned the failures of the provincial, national and of the Inter-American Commission of Law Human beings courts that have established jurisprudence so much national as worldwide of the human rights in the frame of adhesion, of approval; of ratification and of entry into force to the international agreements of right human beings in the National Constitution Argentina. An invocation is to the system of right across one to be able to make and one know, that it does of the Argentine company is characterized by the orders of a juridical speech that enumerates and classifies, it controls and codifies, narrates and pronounces, typifies and condemns or absolves, while human right. Beyond a possible or evident violation to an already established right, the social dynamics demands, by means of a based knowledge, to demand to the structure of the right that it grants subjectivity to the individuals while subject of rights in case of being these they have been ultrajados and that they leave in condition of juridical helplessness, and for ende politician, individuals.